Lifestyle Adjustments and Cardiovascular Health Outcomes - Alanazi, Naifah Oudah; Owdah Alenizi, Rasha; Owdah Alenizi, Nadiah; Alanazi, Reem Awdah; Al Enazi, Nourah Awdah; Oudah Alanazi, Amirah; Tuwialeh Almasoudi, Fatimah; Awadh Alanazi, Najla; Faraj Alotaibi, Mohammed Rashed (Journal of Neonatal Surgery, 2025)
Cardiovascular health is crucial for overall well-being, with cardiovascular diseases (CVDs) posing a significant global burden. Lifestyle adjustments play a pivotal role in preventing and managing CVDs, addressing risk factors such as poor diet, physical inactivity, and chronic stress. Chronic stress, in particular, has been linked to adverse cardiovascular outcomes through physiological and behavioral mechanisms. Effective stress management techniques, including mindfulness, meditation, yoga, and relaxation exercises, offer promising strategies for improving cardiovascular health. Additionally, dietary modifications are integral to cardiovascular health, with heart-healthy diets emphasizing nutrient-rich foods and supporting weight management, blood pressure regulation, and inflammation reduction. Despite the benefits of lifestyle adjustments, individuals may face challenges such as lack of motivation, social influences, socioeconomic factors, and psychological barriers. Implementing behavioral change strategies, such as patient education, behavioral counseling, goal setting, social support, motivational interviewing, and feedback mechanisms, can facilitate the adoption and maintenance of healthier lifestyles, thereby reducing the risk of CVDs and enhancing overall cardiovascular well-being.